You're not crazy--you're codependent eaudiobook What everyone affected by addiction, abuse, trauma or toxic shaming must know to have peace in their lives. - Menter, Jeanette Elisabeth (Tantor Media, 2018)
If your life has been affected by addiction (yours or someone else's), abuse, trauma or toxic shaming, you may also be struggling with another invisible problem—codependency. Without your even being aware of the connection to the above issues, it has created additional life-long challenges such as endless guilt, anxiety, perfectionism, need to control, depression, a history of dysfunctional relationships and much more. This easy to understand, interactive book will reveal how codependency has sobotaged you, the lies it created in your beliefs and the truths that expose them. Also included is a Guide to Recovery using simple acts of mindfulness to overcome harmful habits in your thinking, actions and choices that are keeping you from having peace. Once you understand you are not crazy, just coping with the deep-seated effects of codependency, you will be free to create the life you were always meant to have.